Homocysteine Induces Apoptosis of Rat Hippocampal Neurons by Inhibiting 14-3-3ε Expression and Activating Calcineurin - Wang, Jing; Bai, Xue; Chen, Yongxing; Zhao, Yanxin; Liu, Xueyuan (PLOS ONE, 2012)
A high level of plasma homocysteine (Hcy) increases the risk for neurodegenerative diseases. One such disorder is Alzheimer’s disease, which involves marked neuronal apoptosis of unknown etiology. This study shows that Hcy inhibits expression of 14-3-3ε and activates calcineurin in rat hippocampal neurons in a dose-dependent manner. Calcineurin-mediated Bad dephosphorylation, which is blocked by calcineurin inhibition and Ca2+ chelation, causes mitochondrial translocation of Bad and apoptosis; this step in the apoptotic pathway is synergistically blocked by calcineurin inhibition and overexpression of 14-3-3ε. These findings demonstrated that calcineurin activation and downregulation of 14-3-3ε may be one of the mechanisms of Hcy-induced apoptosis of hippocampal neurons.